Scientometrics of Language Policy in Sustaining Arabic Learning in Indonesia - Ritonga, Apri Wardana; Bahruddin, Uril; Abdullah, Muhammad Yahya; Desrani, Ayu; Ayad, Nahid (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2025)
This study examines the evolution of Arabic language policy in Indonesia, focusing on its historical and political dimensions to assess the sustainability of Arabic language education. The analysis specifically highlights five key revisions to the Arabic language curriculum in the post-reform era, aimed at enhancing the quality of Arabic language instruction in Indonesia. Utilizing Norman Fairclough's Critical Discourse Analysis (CDA), this research explores the historical trajectory of Arabic language teaching from the Dutch East Indies era to the present. The findings reveal that Arabic language policy has undergone significant transformations since the reform period, reflecting the government’s sustained efforts to improve the quality and continuity of Arabic education. The political context plays a crucial role in shaping the classification of students' language proficiency, the objectives of Arabic language learning, and its status as an integral part of religious identity. The study suggests that further research is needed to deepen the understanding of Arabic language policy. Based on bibliometric analysis, it is recommended that future scholars focus on exploring language education policies to broaden the existing literature on this subject.